2011
DOI: 10.1200/jco.2011.29.4_suppl.516
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of preoperative bevacizumab, capecitabine, and radiotherapy for resectable locally advanced rectal cancer.

Abstract: Background: To evaluate whether the addition of bevacizumab (BVZ) to capecitabine-based chemoradiotherapy in the preoperative treatment of locally advanced rectal cancer (LARC) improves efficacy measured by the pathological complete response (pCR) rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One published report described this phenomenon in 2 women treated for metastatic breast cancer and emphasised the importance of recognising this clinically to avoid unnecessary surgery 3 . A phase II study reported that 2 of 43 patients undergoing preoperative combination bevacizumab, capecitabine and radiotherapy in rectal cancer developed paralytic ileus 4 . A phase III study reported that paralytic ileus was the cause of death in a patient with metastatic breast cancer treated with combination capecitabine and docetaxel 5 .…”
Section: Discussionmentioning
confidence: 99%
“…One published report described this phenomenon in 2 women treated for metastatic breast cancer and emphasised the importance of recognising this clinically to avoid unnecessary surgery 3 . A phase II study reported that 2 of 43 patients undergoing preoperative combination bevacizumab, capecitabine and radiotherapy in rectal cancer developed paralytic ileus 4 . A phase III study reported that paralytic ileus was the cause of death in a patient with metastatic breast cancer treated with combination capecitabine and docetaxel 5 .…”
Section: Discussionmentioning
confidence: 99%